2000
DOI: 10.1136/bmj.320.7229.220
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of left ventricular systolic dysfunction in primary care: cross sectional study evaluating a range of diagnostic tests

Abstract: Objectives To assess the probability of left ventricular systolic dysfunction without echocardiography in patients from general practice. Design Cross sectional study using multivariate regression models to examine the relation between clinical variables and left ventricular systolic dysfunction as determined by echocardiography. Setting Three general practices in Copenhagen. Subjects 2158 patients aged > 40 years were screened by questionnaires and case record reviews; 357 patients with past or present signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 22 publications
(21 reference statements)
2
49
0
Order By: Relevance
“…30 Others have also shown that a normal ECG may be useful to exclude heart failure. 5,31 In the present study, the negative predictive value was 94% in a population with 24% systolic dysfunction and only 27% normal ECGs. In our study, an ECG added significant diagnostic accuracy to readily available diagnostic tests (model 2c) even when NT-proBNP was included in the model (3c).…”
Section: Discussionmentioning
confidence: 75%
“…30 Others have also shown that a normal ECG may be useful to exclude heart failure. 5,31 In the present study, the negative predictive value was 94% in a population with 24% systolic dysfunction and only 27% normal ECGs. In our study, an ECG added significant diagnostic accuracy to readily available diagnostic tests (model 2c) even when NT-proBNP was included in the model (3c).…”
Section: Discussionmentioning
confidence: 75%
“…For example, vascular redistribution and cardiomegaly were identifi ed as radiological criteria for diagnosing cardiac failure in one study, 17 whereas another study found no value of radiographic fi ndings in diagnosing heart failure. 18 Local radiologists in the centers associated with each primary care network examined chest radiographs. We aimed for uniform assessments through the use of a protocol for reporting abnormalities in the chest radiographs.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…We intended to use NT-proBNP testing, which can basically be done during routine blood sampling, as a reliable and fast means of risk stratification for mild forms of HF in obesity. Obviously increased NT-proBNP could be an indicator for further and more intense diagnostic procedures because even in nonobese patients with an abnormal electrocardiogram, Nielsen et al (27 ) considered the probability of left ventricular systolic dysfunction based on the combined use of diastolic blood pressure and NT-proBNP concentration without echocardiography. This protocol was accurate enough to identify patients who should be referred to echocardiography (27 ).…”
Section: Discussionmentioning
confidence: 99%